Voices from the Margins : submission to the Australian Government Department of Families, Housing, Community Services and Indigenous Affairs Green Paper. Which Way Home: A New Approach to Homelessness - Holden, Annie; Micah Projects (South Brisbane : Micah Projects Inc., 2008)
This response to the Green Paper has been informed by focus groups with individuals and families who have experienced homelessness, structured interviews with rough sleepers, and the reflections of staff who work directly with these individuals and families. It also includes samples of small project work undertaken to inform practice and future planning in addressing homelessness in Brisbane.
1. Introduction -- 2. Sleeping rough -- 3. Getting housed -- 4. Staying housed -- 5. Support for families -- 6. Early intervention -- 7. Example of research and data -- 8. Practitioners' wisdom.
Title from PDF cover page (viewed on March 20, 2015)
"The report was prepared by Dr Annie Holden." -- page 9.
Available online at the State Library of Queensland.
Includes bibliographical references.
Also available online (as at 20/03/15) at: http://www.micahprojects.org.au/resources/publications.
Available online (as at 20/03/15) at: http://www.micahprojects.org.au/resources/publications.
Keywords: Homelessness -- Queensland -- Brisbane; Homeless persons -- Services for -- Queensland -- Brisbane; Homeless persons -- Queensland -- Brisbane -- Attitudes; Social surveys -- Queensland -- Brisbane